Modelo de dimensionamiento del servicio web hosting dirigido a proveedores de la pequeña y mediana empresa colombiana - Ramírez Calero, Olga Lucía; Torres Acosta, Jairo Humberto (Ingeniería, 2010)
Infrastructure resource management and capacity planning of a web hosting service, which consists on assigning shared resources of a computer server to run multiple websites [21], are achieved at a high cost in terms of large-scale high-availability servers. This is carried out by monitoring capacity indicators that reactively establish the capacity needs, or else, by using redundant IT infrastructure, which implies increasing the number of hardware components to ensure service availability. When providing services intended for small- and mediumscale businesses, it is necessary to meet certain availability requirements at low cost. This paper presents research results on the design, development and validation of a capacity optimization model that allows sizing and selecting the best combination of server infrastructure resources (hard disk, RAM and processor) in a web hosting service, intended for small- and medium-scale businesses in Colombia.